Interaction between insulin and androgen signalling in decidualization, cell migration and trophoblast invasion in vitro. Issue 20 (31st August 2021) - Hirschberg, Angelica Lindén; Jakson, Ivika; Graells Brugalla, Carlota; Salamon, Daniel; Ujvari, Dorina
Abstract: Finely tuned decidualization of endometrial stromal fibroblasts into decidual cells is crucial for successful implantation and a healthy pregnancy. Both insulin and androgens are known to modulate decidualization, however, their complex effect on this process has not been fully elucidated. As hyperinsulinemia and hyperandrogenism are associated in clinical conditions, we aimed to investigate the interaction between insulin and androgens on decidualization. Primary human endometrial stromal cells were decidualized in vitro in the presence of insulin and/or androgens (dihydrotestosterone (DHT), testosterone). Gene or protein expressions of decidualization markers were measured, and cells size characteristics were determined. Migration of decidualizing endometrial stromal cells and invasion of HTR‐8/SVneo trophoblast spheroids were assessed. We found that insulin and androgens in combination enhanced the upregulation of several decidualization markers including prolactin, tissue factor, tissue inhibitor of matrix metalloproteinase 3 and connexin‐43, and also interacted in modulating cell size characteristics resulting in enlarged decidualizing cells. However, insulin and DHT together restricted the migration of decidualizing cells and invasion of trophoblast spheroids. Our findings suggest that insulin and androgens interact to potentiate the process of decidualization. On the other hand, inhibited cell migration and trophoblast invasion might negatively impact the function of decidualizing endometrial stromal cells.